2002
DOI: 10.1007/s00467-002-0898-y
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the criteria for the clinical diagnosis of Gitelman syndrome

Abstract: A 16-year-old female had mutations in both alleles of the gene encoding her sodium-chloride cotransporter; one of these mutations is newly described. Her clinical findings were not typical because of the absence of hypocalciuria in 24-h urine samples, her maximum urine osmolality (U(osm)) was only 802 mosmol/kg H(2)O, and her plasma magnesium (Mg) concentration (P(Mg)) was easily maintained in the normal range with oral Mg supplements for 1 month. In detailed studies, the calcium/creatinine ratio in spot urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Indeed, despite the small size of our study, significant differences were observed between the three groups concerning blood potassium, chloride, magnesium, supine aldosterone and 24 h urine chloride and magnesium levels. However, hypomagnesaemia and hypocalciuria were not constant, which is in line with other previous studies in which the absence of hypomagnesaemia reached 20-40% and the absence of hypocalciuria 26% (24)(25)(26)(27)(28). Indeed, numerous factors can interfere with urinary calcium excretion, such as calcium, salt and protein intake; age; vitamin D level and other gene polymorphisms such as the CaSR gene (29).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, despite the small size of our study, significant differences were observed between the three groups concerning blood potassium, chloride, magnesium, supine aldosterone and 24 h urine chloride and magnesium levels. However, hypomagnesaemia and hypocalciuria were not constant, which is in line with other previous studies in which the absence of hypomagnesaemia reached 20-40% and the absence of hypocalciuria 26% (24)(25)(26)(27)(28). Indeed, numerous factors can interfere with urinary calcium excretion, such as calcium, salt and protein intake; age; vitamin D level and other gene polymorphisms such as the CaSR gene (29).…”
Section: Discussionsupporting
confidence: 88%
“…Although the coexistence of hypomagnesemia and hypocalciuria is typical for NCCT deficiency, it is neither a specific nor universal finding. Clinical observations in NCCT-deficient patients disclosed intraindividual and interindividual variations in urinary Ca 2ϩ concentrations, which can be attributed to gender, age-related conditions of bone metabolism, intake of Mg 2ϩ supplements, changes in water diuresis and urinary osmolality, respectively (68,91). Likewise, hypomagnesemia might not be present from the beginning.…”
Section: Thiazide-sensitive Na ϩ -Cl ϫ Cotransportermentioning
confidence: 99%
“…263800) is an autosomal-recessively inherited renal tubular disorder characterized by low plasma potassium and magnesium levels, reduced calcium excretion, metabolic alkalosis and increased renin activity associated with normal blood pressure levels. Hypocalciuria and hypomagnesemia are typical features of patients with GS; however, they are not constant findings in GS [1]. In a majority of patients, the GS phenotype is caused by mutations in the SLC12A3 gene (MIM No.…”
Section: Introductionmentioning
confidence: 99%